ÉPOCA DE SEMEADURA PARA A CULTURA DO CRAMBE PARA INFERÊNCIAS À REGIÃO NOROESTE DO RIO GRANDE DO SUL - Silva, José A. G. d.; Krüger, Cleusa A. M. B.; Bandeira, Taiane P.; Viau, Luiz V. M.; Manjabosco, Cíntia D.; Mazurkievicz, Gustavo (Salão do Conhecimento, 2013)
Resumo